Distributed control and resource marking using best-effort routers. - Gibbens, R. (IEEE Network : the magazine of global information exchange)
We present a method for creating differential QoS where control is in the hands of the end system or user, and the network distributes congestion feedback information to users via packet marking at resources. Current proposals for creating differential QoS in the Internet often rely on classifying packets into a number of classes with routers treating different classes appropriately. The router plays a critical role in guaranteeing performance. In contrast, there is a growing body of work that seeks to place more of the control in the hands of the end system or user, with simple functionality in the router. This is the approach outlined in this tutorial article: using insights from economics and control theory we show how cooperation between end systems and the network can be encouraged using a simple packet marking scheme. The network distributes congestion feedback information to users via packet marking at resources, and users react accordingly to obtain differential QoS